Emergence of the brain-border immune niches and their contribution to the development of neurodegenerative diseases - Tan, Li Yang; Cunliffe, Grace; Hogan, Michael Patrick; Yeo, Xin Yi; Oh, Chansik; Jin, Bohwan; Kang, Junmo; Park, Junho; Kwon, Min-Soo; Kim, MinYoung; Jung, Sangyong (Frontiers in Immunology, 2024)
Historically, the central nervous system (CNS) was regarded as 'immune-privileged', possessing its own distinct immune cell population. This immune privilege was thought to be established by a tight blood-brain barrier (BBB) and blood-cerebrospinal-fluid barrier (BCSFB), which prevented the crossing of peripheral immune cells and their secreted factors into the CNS parenchyma. However, recent studies have revealed the presence of peripheral immune cells in proximity to various brainborder niches such as the choroid plexus, cranial bone marrow (CBM), meninges, and perivascular spaces. Furthermore, emerging evidence suggests that peripheral immune cells may be able to infiltrate the brain through these sites and play significant roles in driving neuronal cell death and pathology progression in neurodegenerative disease. Thus, in this review, we explore how the brain-border immune niches may contribute to the pathogenesis of neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), and multiple sclerosis (MS). We then discussed several emerging options for harnessing the neuroimmune potential of these niches to improve the prognosis and treatment of these debilitative disorders using novel insights from recent studies.